Kick Frequency and Velocity Finswimming Analysis In Surface 100 Meter Number Reviewed From Stiffness Monofins Hard and Stiffness Monofins Exstra Hard Characteristics - Rizkia, Fikri; Sutresna, Nina; Mulyana, Raden Boyke; Sya'rani, Ahmad Zaeri (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2021)
Finswimming is a water sport that is done using assistive devices, such as bins, monofins, and snorkels. The fastest sport that is carried out in the pool is getting more and more enthusiasts and is starting to attract a lot of attention in its activities. The growing development of this sport makes manufacturers of monofins tools increasingly develop the types of stiffness that are presented, including stiffness monofins hard and stiffness monofins extra hard. The purpose of this study was to analyze the kick frequency and velocity in the number 100 Meter surface in terms of the characteristics of the stiffness monofins hard and the stiffness monofins extra hard. This research method is descriptive quantitative with a cross-sectional research design. The population of this research is finswimming athletes in Bandung, purposive sampling technique is used to determine the sample with several criteria. The sample consisted of 16 athletes with the following criteria: (1) Bandung City Finswimming Athletes had practiced monofins for at least three years. (2) had monofins stiffness hard and extra hard. (3) is in the top 20 of the inter-regional championship monofins. The conclusion of this study, the stiffness monofins hard and stiffness monofins extra hard contributed less to the kick frequency, while on the velocity both had an effect and the stiffness monofins hard gave a greater influence with a percentage of 98.3%.